LOCAL BASED PERFORMANCE DALAM IMPLEMENTASI KEBIJAKAN PELAYANAN TERPADU SATU PINTU KABUPATEN KEPULAUAN ARU PROVINSI MALUKU - Karolina Morwarin; Andries Lionardo (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2022)
The demands for solving public problems have shifted the viewpoint of the role of the government as the sole provider of services towards participatory governance as a form of democracy that can adapt to change. These demands must be addressed wisely by reconciling the expectations of the community and organizational capabilities, as well as reducing bias in the capacity of public organizations as service providers. This study identified the factors that work in the process of implementing integrated service policy in an archipelago in facing the transformation of ICT-based services, analyzed the ability and commitment of one-door integrated service (PTSP) implementers, coordination patterns, private sector cooperation, and community participation in services so that it can provide a holistic and complete picture of implementation. The method used was descriptive qualitative by determining informants using purposive sampling. The data were collected through in-depth interviews, observation, and document study. Next, semantic coding was carried out using the NVivo 12 Plus to determine the categories/themes to be generalized. The results of the study reveal that there is a community culture that encourages the mobile PTSP service system by GA and the involvement of NGA who works voluntarily and in business. Public support is very high, but the implementation performance has not yet reached the goal of self-help service (OSS) policy due to technical constraints, namely geographical distance, equipment, and budget.Keywords: cultural, commitment, informal, policy implementation